A survey of usability awareness in IT industry - Hussein, Idyawati; Mahmud, Murni; Md. Tap, Abu Osman (2011)
This paper reports a survey result of usability awareness in the information technology (IT) industry. The survey involved 72 personnel who were IT-practitioners, non-IT practitioners and IT students based on their involvement in the IT development process. Generally, they require more exposure to understand the usability importance and practice. Result reveals there is no significant different on the usability awareness between IT practitioners (e.g. software developer, system analyst etc.), non-IT practitioners (e.g. sales and marketing personnel) and IT student in IT industry. Finding indicates that usability is perceived as a “common sense” knowledge for both IT and non- IT practitioners. The international standard for usability is lacking in the IT development projects. The degree of recognition of Human-Computer Interaction (HCI) and usability terminology is higher than expected, but the practice towards usability received lack attention. Profiles from the students who work as trainee and non-IT personnel indicated a relatively high condition on blaming themselves for not understanding current system interfaces in use. This study provides an indication of current usability awareness following user-experience (UX) development